Updates in head and neck cancer: one year in review - Aline L. F. Chaves; William N. William; Gustavo N. Marta; Diego C. R. Morais; Gilberto de Castro; Vinicius C. Souza; Eduardo D. de Moraes; Thiago B. de Oliveira; Luiz P. Kowalski (Brazilian Journal of Oncology)
Introduction: Head and neck squamous cell carcinoma (HNSCC) encompass a heterogeneous group of tumors with a challenge treatment. In Brazil, HNSCC represent the third most frequent neoplasia in men. Aim: The aim of this study was to review the most relevant and practice changing articles recently published. Material and methods: The review of the literature covered studies published over the last year and described key evidence-based changes in treatment of HNSCC. Results: We retrieved nine studies with clinical impact. The main updates include: 1) systematic review in the treatment delivery time; 2) recommendations for the diagnosis of HPV oropharyngeal carcinoma; 3) guidelines for the delineation of target volumes in radiation therapy; 4) de-intensification of treatment in HPV positive oropharyngeal carcinoma; 5) induction chemotherapy; 6) immunotherapy. Conclusions: The treatment and diagnosis of HNSCC has changed over the last year, mainly with the inclusion of HPV positive oropharyngeal carcinoma and immunotherapy.